Chitinolytic enzymes: an appraisal as a product of commercial potential - Chavan, S. B.; Deshpande, Mukund V. (Biotechnology Progress, 2013)
Chitin, its deacetylated form, chitosan and chitinolytic enzymes viz. endo-chitinase, N-acetylglucosaminidase, chitosanase, chitin deacetylase (CDA) are gaining importance for their biotechnological applications. Presently, chitin degrading enzymes constitute high-cost low-volume products in human health care and associated research. Indeed chitinases and CDA-chitosanase complex possesss tremendous potential in agriculture to control plant pathogenic fungi and insects. The success in exploring chitinases especially for agriculture, i.e. as a high-volume low-cost product, depends on the availability of highly active preparations with a reasonable cost. Therefore, a reconsideration in terms of understanding the roles of chitinolytic enzymes in applications, e.g. host-pathogen interaction for biocontrol, different mechanisms of chitin degradation, and identification of new enzymes with varying specificities, may make them more useful in a variety of commercial processes in the near future. The possible issues and challenges encountered in the translation of proof of concept into a commercial product will be appraised in this review. (c) 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:833-846, 2013
Keywords: chitin deacetylase; chitinase; chitosanase; high-cost low-volume product; high-volume low-cost product